Student teachers' difficulties in implementing lesson plan during teaching internship - Prasetyanti, Rahmanissa Nurul Hikmah; Rismiyanto, Rismiyanto; Sulistyowati, Titis (Journal of English Language Teaching and Learning (JETLE), 2025)
The teaching internship program is designed to help students develop into professional educators and effectively implement their lesson plans. During the 2024/2025 academic year, English student teachers from Muria Kudus University participated in a teaching internship program at SMA 1 Mejobo. However, implementing their lesson plans in a real classroom was not easy. The objective of this research is to determine whether English student teachers face difficulties when implementing their lesson plans during the teaching internship. This study uses a qualitative descriptive approach with a case study method. The data sources consist of seven participants from seventh-semester English Education students who are participating in the teaching internship program at SMA 1 Mejobo and were selected using purposive sampling (homogeneous). Data were collected through two instruments: questionnaires and semi-structured interviews, then analyzed using thematic analysis, and verified by the participants. The results of the study revealed that student teachers still face several difficulties, such as a lack of experience, limited time, poor classroom control, inadequate teaching media, and so on. The researcher concluded that student teachers had difficulties in implementing lesson plans during teaching internship program